Narodowy system innowacyjności jako filar gospodarki opartej na wiedzy - Zorska, Anna (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2012)
Growth of the knowledge-based economy has been influenced by economic and technological processes in the contemporary world, particularly globalization and information revolution. Research and development activities, knowledge, new technologies and innovations have assumed a crucial significance at all levels of economic activity and for that reason are supported by government policies. According to a World Bank concept growth of the knowledge-based economy can be stimulated by four groups of determinants – or so-called pillars – including: economic and institutional system of a given country, education and training, information infrastructure and national innovation system. Activity of the innovation system promotes creation and diffusion of new knowledge and its application as innovations by national enterprises in co-operation with universities, research centers and public institutions. The activities of all entities can be stimulated by government innovation policies. The problems of national innovativeness are discussed from theoretical and empirical viewpoints, focusing on experience of Finland which is one of the leading countries in world’s rankings of knowledge economy and national innovation systems. The final conclusion underlines the fact that cross-border linkages of innovation systems within enterprises and countries can generate some threats to a national economy during global economic crisis.